2016
DOI: 10.1007/s00167-016-4140-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient selection criteria for outpatient joint arthroplasty

Abstract: Clinical review, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 32 publications
0
41
0
1
Order By: Relevance
“…Specific patient factors and comorbidities have been identified that should require IP admission for TKA due to an increased risk of perioperative complications, including age > 75 years, uncontrolled diabetes, chronic obstructive pulmonary disease, high body mass index (BMI) (>35 kg/m 2 ), chronic opioid use, functional neurological impairments, dependent functional status, low preoperative cognitive capacity, congestive heart failure, liver cirrhosis, and chronic kidney disease. 14,28,29 Ideally, the optimal OP primary TKA candidate should have a BMI < 35 kg/m 2 , American Society of Anesthesiologists classification <3, strong social support system with an available "coach" for the first 2 postoperative weeks, be able and willing to participate in an OP program, and be < 75 years of age. 28,30 Further cohort investigations are critical to define the best candidates for safe, successful OP TKA.…”
Section: Risks Of Outpatient Tkamentioning
confidence: 99%
See 1 more Smart Citation
“…Specific patient factors and comorbidities have been identified that should require IP admission for TKA due to an increased risk of perioperative complications, including age > 75 years, uncontrolled diabetes, chronic obstructive pulmonary disease, high body mass index (BMI) (>35 kg/m 2 ), chronic opioid use, functional neurological impairments, dependent functional status, low preoperative cognitive capacity, congestive heart failure, liver cirrhosis, and chronic kidney disease. 14,28,29 Ideally, the optimal OP primary TKA candidate should have a BMI < 35 kg/m 2 , American Society of Anesthesiologists classification <3, strong social support system with an available "coach" for the first 2 postoperative weeks, be able and willing to participate in an OP program, and be < 75 years of age. 28,30 Further cohort investigations are critical to define the best candidates for safe, successful OP TKA.…”
Section: Risks Of Outpatient Tkamentioning
confidence: 99%
“…14,28,29 Ideally, the optimal OP primary TKA candidate should have a BMI < 35 kg/m 2 , American Society of Anesthesiologists classification <3, strong social support system with an available "coach" for the first 2 postoperative weeks, be able and willing to participate in an OP program, and be < 75 years of age. 28,30 Further cohort investigations are critical to define the best candidates for safe, successful OP TKA.…”
Section: Risks Of Outpatient Tkamentioning
confidence: 99%
“…It is important to select appropriate candidates and optimize Primary Total Knee Arthroplastyevery facet of their condition [7]. There are several key factors that should be considered to minimize the risks of complications and comorbidities [8].…”
Section: Preoperative Managementmentioning
confidence: 99%
“…Such optimization is also known as 'outpatient joint arthroplasty' , a multimodal clinical pathway based on well-defined patient selection criteria [1][2][3] with the focus on discharge on the day of surgery while ensuring patients' safety [1,[4][5][6][7][8] and cost reduction [9,10,11]. Results have shown that quality of life after TKA, significantly improved within one year postoperative [11].…”
Section: Introductionmentioning
confidence: 99%